Single vs Repeat Surgical Skin Preparations for Reducing Surgical Site Infection After Total Joint Arthroplasty: A Prospective, Randomized, Double-Blinded Study - KÜÇÜKDURMAZ, FATİH; Morrison, Tiffany N.; Chen, Antonia F.; Taneja, Mayank; Kucukdurmaz, Fatih; Rothman, Richard H.; Parvizi, Javad (My University, 2016)
Background: Preventing surgical site infection (SSI) after total joint arthroplasty (TJA) is a high priority and is partly linked to the efficacy of surgical site preparation solutions (SPSs) in reducing the number of pathogens on the skin before incision. The aim of this study is to investigate the effectiveness of SRS reapplication after draping to reduce the incidence of SSI after TJA.